A new species of Bryophryne (Anura: Strabomantidae) from the Cordillera de Vilcabamba, southeastern Peruvian Andes - Mamani, Luis (2017)
A new species of Bryophryne (Anura: Strabomantidae) from the Cordillera de Vilcabamba, southeastern Peruvian Andes. We describe a new species of Bryophryne from the Cordillera de Vilcabamba in Department Cusco, in the southeastern Peruvian Andes. The new species differs from all other congeneric taxa, except B. flammiventris and B. gymnotis, by possessing a weakly defined tympanic membrane and tympanic annulus, by the presence of vocal sac and vocal slits in males, and by producing advertisement calls. The new species is distinguished from B. flammiventris and B. gynznotis by skin texture, presence of small, oblique dentigerous processes on the vomer, ventral coloration ranging from bluish-gray to whitish-gray with irregular or reticulate dark brown spots, and call composed of two or three notes. The new species is further characterized by having dorsal skin shagreen with tubercles, discontinuous dorsolateral folds, skin smooth on ventral surfaces of the body, and lateral fringes on fingers and toes. This species was found at the transition from montane forest to high Andean pupa, where it occurs in moist microhabitats under moss and rocks at elevations from 3519 to 3707 m a.s.l.